A systematic review of the diagnostic accuracy of Loop-mediated-isothermal AMPlification (LAMP) in the diagnosis of invasive meningococcal disease in children - Thomas Waterfield; Derek Fairley; Bronagh Blackwood; James McKenna; Michael D. Shields (BMC, 2019)
Abstract Background The early recognition of meningococcal disease in children is vital. During the prodrome however, meningococcal infection presents similarly to many self-limiting viral infections. This mandates a cautious approach with many children receiving unnecessary broad-spectrum parenteral antibiotics. Advances in nucleic acid amplification techniques mean that it is now possible to test for Neisseria meningitidis DNA using Loop-mediated-isothermal AMPlification (LAMP). This technique is quicker than traditional PCR techniques and can be performed using simple equipment. Methods Prior to performing this systematic review, a protocol was developed adhering to PRISMA P standards and underwent full external peer review. This systematic review was registered with PROSPERO (CRD42017078026). The index test assessed was LAMP for Neisseria meningitidis and the reference standard was culture or qPCR of a sterile site detecting Neisseria meningitidis. Results We identified 95 records in total: 94 records from the electronic databases and 1 additional study from the grey literature. After removal of duplicates, 36 studies were screened, and 31 studies excluded based on the title/abstract. Five full text studies underwent full text review and three studies, including 2243 tests on 1989 patients aged between 7 days and 18 years were included in the final systematic review. In all studies the LAMP assay and qPCR primers were directed against the ctrA region of the Neisseria meningitidis bacteria. The diagnostic accuracy of LAMP testing for invasive meningococcal disease was reported as high (sensitivity 0.84-1.0 and specificity 0.94-1.0) in all studies irrespective of the sample tested (CSF, Blood, Swab). Conclusions We included three studies with 2243 tests on 1989 patients using CSF, blood samples or naso/oropharyngeal swabs. The studies were all of a high quality and deemed at low risk of bias. Results show that LAMP testing on blood and CSF was highly accurate when compared to qPCR/culture. LAMP testing for Neisseria meningitidis is fast and highly accurate and therefore has the potential to be used to rapidly rule in/out meningococcal disease in children. Given the life-threatening nature of meningococcal infection further research is required to demonstrate the safety and efficacy of using LAMP testing for Neisseria meningitidis as a rule in/out test. Trial registration This systematic review was registered prospectively with PROSPERO on the 29/11/2017 (CRD42017078026).